Avaliação do tratamento da anemia em pacientes com insuficiência renal crônica em hemodiálise em uso de eritropoetina, ferro oral e endovenoso - Escorcio, Carla Solange de Melo (2005)
The object of this study was to compare the effectiveness of polynuclear iron (III) hydroxide sucrose complex, administered intervenously, with iron sulfate in the treatment of anemia in 89 patients with chronic renal insufficiency in hemodialysis, with r-HuEPO, in Fortaleza from January 2004 to January 2005. It was a transversal prospective study conducted in two hemodialysis clinics in Fortaleza – Ceará .the data were collected from the patients medical charts and expressed as arithmetic mean + - SD. In accordance with treatment, the patients were grouped in terms of treatment :oral and intervenous iron, and intervenous iron. The following parameters were analyzed during the study: age, gender, length of dialysis , baseline, hemogloibin, hematocrit , serum iron , serum ferritin, saturation level of transferrina, latent capacity and bonding of iron. It was establish that there occurred no superior effectiveness with polynuclear iron (III) hydroxide sucrose complex, administered intervaneously, in the treatment of anemia in patients with IRC in hemodialysis, in the use of r-HuEPO. The analyzed parameters during the study verified indirectly the supply of iron. Consequently, it was not possible to establish a confident and precise determination of the deficiency or oversupply of iron in these patients.